2020
DOI: 10.1016/j.ejca.2019.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organised cervical cancer screening on cervical cancer mortality in Europe: a systematic review

Abstract: a on behalf of the EU-TOPIA consortium 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
122
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(132 citation statements)
references
References 38 publications
2
122
0
8
Order By: Relevance
“…According to the International Agency for Research on Cancer (IARC), CCS programs have been shown to be an effective strategy to reduce the incidence of the disease [4,[6][7][8]. Evidence shows that cervical cancer mortality was reduced in European countries that implemented organized CCS programs [9]. Reduction in cervical cancer incidence and mortality in opportunistic screening ranged from 10 to 60% worldwide [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Agency for Research on Cancer (IARC), CCS programs have been shown to be an effective strategy to reduce the incidence of the disease [4,[6][7][8]. Evidence shows that cervical cancer mortality was reduced in European countries that implemented organized CCS programs [9]. Reduction in cervical cancer incidence and mortality in opportunistic screening ranged from 10 to 60% worldwide [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer represents one of the most important issues worldwide. The estimated incidence in Europe is 10.6 per 100,000 [1]. Cervical cancer represents a source of ongoing concern for the health care since it correlates with a high mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer represents a source of ongoing concern for the health care since it correlates with a high mortality rate. And it is one of the most preventable type of cancer because it develops over a long time [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the vaccine era, organized cervical cancer screening remains one of the most effective measures to reduce cervical cancer incidence and mortality. 1 Liquid-based cytology (LBC) and HPV test are the two most common cervical screening strategies. In spite of the inherent advantages of LBC in cervical screening, the low sensitivity of LBC often causes missed diagnosis.…”
Section: Introductionmentioning
confidence: 99%